Profile of Students' Proportional Reasoning in Solving Mathematics Problems Based on Field Independent-Dependent Cognitive Style - Riandika Davis Kurnia Putra; Susanah Susanah (MATHEdunesa, 2026)
This study aims to describe the profile of students' proportional reasoning in solving mathematical problems in terms of field independent and field dependent cognitive styles. Proportional reasoning is a logical thinking process in developing strategies that involve understanding covariation and multiplicative relationships in situations of comparing two or more quantities. The subjects of this study were one student with a field independent cognitive style and one student with a field dependent cognitive style who were of the same gender and had the same level of mathematical ability. The instruments used were mathematical problem assignments and interview guidelines. The instruments used have been consulted with the supervising lecturer and validated by partner teachers. The analysis focused on indicators of proportional reasoning: understanding covariation, recognizing proportional situations, applying multiplicative strategies, and using ratios correctly. The results of this study indicated that the independent student demonstrated a strong grasp of covariation, effectively recognized proportional situations, employed unit rate strategies for problem-solving, and accurately understood ratio usage. Conversely, the dependent student also understood covariation but struggled with recognizing proportional situations, could not determine comparison types, used unit rate strategies, and had a less accurate understanding of ratios due to illogical reasoning.